FACTORS THAT AFFECT THE UTILIZATION OF SERVICES BY OUTPATIENTS AT HOSPITALS. TENGKU CHIK DITIRO - Kartika, Kartika; Sitepu, Meriahta; Nasution, Ramadhani Syafitri (HEARTY, 2026)
The use of health services is the use of service facilities provided, both in the form of outpatient care, hospitalization, and home visits by health workers. This study aims to analyze the factors that affect the utilization of outpatient services at Tengku Chik Ditiro Hospital.This study uses an analytical survey design with a cross-sectional approach. The study population was all outpatients totaling 112 people, with sampling techniques using accidental sampling. Data analysis was carried out univariately, bivariate using chi-square test, and multivariate using logistic regression test with a significance level of α = 0.05.The results showed that of 93 respondents, the majority had a perception of disease in the bad category as many as 47 people (50.5%), a perception of health services in the bad category as many as 56 people (60.2%), and a perception of clinical diagnosis in the good category as many as 63 people (67.7%), The attitude of medical workers in the bad category was 53 people (57.0%), the availability of drugs and medical devices in the bad category was 54 people (58.1%), and the utilization of outpatient services by non-poor patients was 50.8%. The variable that affects the utilization of outpatient services at Tengku Chik Ditiro Hospital is the perception of clinical diagnosis.